The Effectiveness of Applying the Practice Rehearsal Pair (PRP) Method in Teaching Speaking - Joni Helandri; Rambat Nur Sasongko; Muhammad Kristiawan (Linguistic, English Education and Art (LEEA) Journal, 2021)
The objective of this study was to find out whether or not it was significantly effective to teach speaking by applying the Practice Rehearsal Pair (PRP) method to the third-semester students of STAI Bumi Silampari Lubuklinggau in the academic year of 2019/2020. The technique used was quasi-experimental with one group pre-test post-test design. The results of this study were; (1) the mean students’ score in the pre-test was66.70; (2) the mean score of post-test was 83.87; (3) the result of paired t-test was 10,925, which was higher than the 1.697 value of the t table of 30 with 95% significant level for one tailed-test. In conclusion, the result of the research was significantly effective in teaching speaking by applying the Practice Rehearsal Pair (PRP) method to the third-semester students of STAI Bumi Silampari Lubuklinggau in the academic year of 2019/2020. Keywords: Applying, Effectiveness, Practice Rehearsal Pair (PRP) Method, Teaching Speaking